Capacitive performance of electrodeposited PEDOS and a comparative study with PEDOT. (1st December 2016) - Liu, Hongtao; Zhou, Weiqiang; Ma, Xiumei; Chen, Shuai; Ming, Shouli; Lin, Kaiwen; Lu, Baoyang; Xu, Jingkun
Graphical abstract: Poly(3, 4-ethylenedioxyselenophene) (PEDOS) prepared via electropolymerization was investigated as an active electrode material for supercapacitor in 0.1 M CH3 CN-LiClO4 and compared with PEDOT under the same conditions. The resultant polymers were characterized by EQCM, FT-IR, SEM, CV, and EIS. Although EDOS possessed higher molar mass which may result in lower specific capacitance in theory, but the higher doping level ( y  = 0.53) make the specific capacitance of PEDOS over that of PEDOT. Based on this, PEDOS have had the potential to become a good supercapacitor material. Highlights: PEDOS was investigated as a novel and active supercapacitor electrode material. PEDOS film electrode afforded good specific capacitance. The different capacitive performance between PEDOS and PEDOT were explained. Abstract: Poly(3, 4-ethylenedioxyselenophene) (PEDOS) prepared via electropolymerization was investigated as an active electrode material for supercapacitor in 0.1 M CH3 CN-LiClO4 . Meanwhile, Poly(3, 4-ethylenedioxythiophene) (PEDOT) as a contrast was prepared and measured under the same conditions. The resultant polymers were characterized by EQCM, FT-IR, SEM, CV and EIS. Although EDOS possessed higher molar mass which may result in lower specific capacitance in theory, but the higher doping level ( y  = 0.53) make the specific capacitance of PEDOS over that of PEDOT. Based on this, PEDOS has the potential to become a good supercapacitor material. The compact PEDOS electrode afforded a higher specific capacitance of 208 F g −1 at 25 mV s −1 compared with PEDOT (205 F g −1 ). Furthermore, the specific capacitance of the symmetric full cell based on two PEDOS electrodes reached 42.02 F g −1 at 25 mV s −1 .